1973
DOI: 10.1111/j.1469-8137.1973.tb04395.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF ROOT PRUNING AND 6‐BENZYL‐AMINOPURINE ON THE CHLOROPHYLL CONTENT, 14CO2 FIXATION AND THE SHOOT/ROOT RATIO IN SEEDLINGS OF PISVM SATIVUM L.

Abstract: SUMMARYPruning the roots of light-grown pea seedlings every 4 days accelerated senescence of older leaves and reduced their rate of fixation of '*C02. Application of 6-benzylaminopurine to the shoot largely compensated for root removal and increased the shoot/root ratio of both pruned and intact plants. It is suggested that the supply of cytokinins from root to shoot may affect leaves by delaying senescence and maintaining tlieir capacity for photosynthesis; it may also alter the distribution of dry matter wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

1976
1976
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…Although cytokinins were not specifically identified as the active regulating component, several studies have shown that roots or factors from the roots are required for maintaining leaf Chl content (18) and photosynthesis (4,5,18,27). In Phaseolus, foliar applications of BA delayed Chl loss and photosynthetic decline associated with senescence (1).…”
Section: Grpahymentioning
confidence: 99%
See 1 more Smart Citation
“…Although cytokinins were not specifically identified as the active regulating component, several studies have shown that roots or factors from the roots are required for maintaining leaf Chl content (18) and photosynthesis (4,5,18,27). In Phaseolus, foliar applications of BA delayed Chl loss and photosynthetic decline associated with senescence (1).…”
Section: Grpahymentioning
confidence: 99%
“…In Perilla, there was a 5-fold increase in cytokinin-like activity in root pressure exudate after floral induction (2, 3). Conversely, the root sap of Xanthium plants which had been induced to flower contained less than onethird as much cytokinin-like activity as did the sap of vegetative plants (24).Although cytokinins were not specifically identified as the active regulating component, several studies have shown that roots or factors from the roots are required for maintaining leaf Chl content (18) and photosynthesis (4,5,18,27). In Phaseolus, foliar applications of BA delayed Chl loss and photosynthetic decline associated with senescence (1).…”
mentioning
confidence: 99%
“…Cytokinin-driven diversion of assimilates and mineral nutrients towards shoot meristems, rather than to roots, ultimately resulting in a differential increase in aerial biomass has been reported for a wide number of species [9][10][11][12][13], including ornamental plants [14,15]. Plant tissues and organs rich in cytokinins, like the stem apical meristem, are known to attract photoassimilates [16].…”
Section: Introductionmentioning
confidence: 99%
“…root system (Table 2) at some stage at least of their lifecycle. Indeed recent research has shown tbat the roots are more to a plant than simply an absorption or an anchorage mechanism, being also the site of synthesis of organic compounds responsible for the whole growth of the shoot (McDavid, Sagar & Marshall, 1973) and any reduction in the root size or growth may affect assimilation, growth and development. Ozenda (1965) classified flowering parasites into cither holoparasites or hemiparasites depending on their possession of chlorophyll.…”
Section: Diseussionmentioning
confidence: 99%